МИРОВОЙ ОПЫТ НЕЧЕТКОГО МАТЕМАТИЧЕСКОГО МОДЕЛИРОВАНИЯ САМОСТОЯТЕЛЬНОЙ РАБОТЫ СТУДЕНТОВ В ЦИФРОВОЙ ОБРАЗОВАТЕЛЬНОЙ СРЕДЕ - Сеитназаров, К.К.; Ауезова, Р.К.; Сабуров, М.С. (SCIENCE and SOCIETY, 2025)
In the context of the rapid development of digital educational technologies, the problem of objective and justified assessment of students' independent work is becoming particularly relevant. The purpose of this dissertation research is to develop and scientifically substantiate a methodology for assessing students' independent work in a digital educational environment using fuzzy mathematical modeling methods.
Keywords: digital education; independent work; fuzzy modeling; LMS Moodle system; independent learning methodology